Effects of Cadmium on Oxidative Stress Markers, and Insulin Secretion and Content in Pancreatic Isolated Islet of Rats - Mojtaba Sargazi; Fatemeh Zal; Narges Karbalaei (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Cadmium is a highly toxic industrial and environmental pollutant that is known as an important risk factor for developing diabetes. Oxidative stress is reported to be highly associated with diabetes and its complications. The aim of this study was to evaluate the effects of cadmium on oxidative stress response and secretory function of islets of Langerhans from rat pancreas. Materials and methods: Male Sprague-Dawley rats weighing 260-230 g, were divided into two groups, including a control and an experimental group that received cadmium chloride. After intraperitoneal glucose tolerance test (IPGTT) on day 30, the animals were deeply anesthetized and the pancreas was removed for pancreatic islet isolation. Oxidative stress, islet insulin content and secretion were also evaluated in pancreas. Results: The findings showed a significant increase in blood glucose concentration and significant decreases in body weight, blood insulin level, insulin content, and secretion of pancreatic islet in response to glucose concentrations in cadmium exposed group compared with those of the control group (P< 0.05). We found that the effects of cadmium on the parameters of oxidative stress led to a significant increase in level of MDA and significant decrease in GSH and activity of antioxidant enzymes in pancreas tissue (P< 0.05). Conclusion: In this study, cadmium led to increase in oxidative stress which can be an important factor in the decreased insulin synthesis and secretion from pancreatic beta cells.